2022
DOI: 10.1098/rsos.220247
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced durability of round bamboo treated with copper naphthenate under heat-cold impregnation

Abstract: Round bamboo has aroused much interest in construction for its mechanical properties, but poor biological durability seriously restricts its application. In order to develop a suitable and effective preservative treatment method for round bamboo, copper naphthenate (CuN) was adopted and impregnated into round bamboo using heat-cold procedure. The distribution and retention of copper naphthenate in round bamboo were studied, and the biological durability represented by the mould and decay resistance were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…The decrease in surface hardness is likely due to hemicellulose degradation caused by heating. Jiang et al [93] performed Copper naphthenate (CuN) impregnation and oil on bamboo specimens and observed that the application of CuN during heat-cold impregnation enhanced the termite resistance of bamboo significantly. Compared to the untreated control, heat oil treatment, and heat-cold impregnation of mineral oil alone, the CuN-treated round bamboo showed notable improvements in decay and mold resistance.…”
Section: Chemical Treatment Methodsmentioning
confidence: 99%
“…The decrease in surface hardness is likely due to hemicellulose degradation caused by heating. Jiang et al [93] performed Copper naphthenate (CuN) impregnation and oil on bamboo specimens and observed that the application of CuN during heat-cold impregnation enhanced the termite resistance of bamboo significantly. Compared to the untreated control, heat oil treatment, and heat-cold impregnation of mineral oil alone, the CuN-treated round bamboo showed notable improvements in decay and mold resistance.…”
Section: Chemical Treatment Methodsmentioning
confidence: 99%
“…This process can enhance bamboo resistance to corrosion, cracks, and improve its overall appearance. Impregnation modification can also be employed to confer bamboo with fire resistance, insect repellent properties, energy storage, and other special characteristics, making it suitable for various specialized applications [57][58][59][60].…”
Section: Impregnation Modificationmentioning
confidence: 99%